Process Management A Multi-disciplinary Guide to Theory, Modeling, and Methodology - Damij, Nadja; Damij, Talib; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Process management affects the functioning of every organization and consequently affects each of us. This book focuses on the multi-disciplinary nature of process management by explaining its theoretical foundations in relation to other areas such as process analysis, knowledge management, and simulation. A crucial linkage between theory and concrete methodology of Tabular Application Development (TAD) is presented as a practical approach consisting of five phases that deal with process identification and modeling, process improvement, development of a process management system and finally - monitoring and maintenance. This book is important for researchers and students of business and management information systems, especially those dealing with courses on process management or related fields. Managers and professionals in process management will also find this book to be useful for their everyday business.
Business Process -- Business Process Modeling -- Business Process Approaches -- Process Analysis -- Knowledge Management -- Simulation -- Data Modeling -- Phase 1: Process Identification -- Phase 2: Process Modeling -- Phase 3: Process Improvement and Innovation -- Phase 4: System Development -- Phase 5: Maintenance -- Case Study -- Phase 4: Systems Development.
Keywords: Economics; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Organization/Planning.; Information Systems Applications (incl. Internet).